Alterations in cathepsin L expression in lung cancers. Issue 7 (21st June 2016) - Okudela, Koji; Mitsui, Hideaki; Woo, Tetsukan; Arai, Hiromasa; Suzuki, Takehisa; Matsumura, Mai; Kojima, Yoko; Umeda, Shigeaki; Tateishi, Yoko; Masuda, Munetaka; Ohashi, Kenichi
Abstract : We herein investigated the potential role of cathepsin L in lung carcinogenesis. Lung cancer cell lines and surgically resected tumors were examined for the expression of the cathepsin L protein and copy number alterations in its gene locus. Cathepsin L was stably expressed in bronchiolar epithelial cells. Neoplastic cells expressed cathepsin L at various levels, whereas its expression was completely lost in most of the lung cancer cell lines (63.6%, 7/11) examined. Furthermore, expression levels were lower in a large fraction of lung tumors (69.5%, 139/200) than in bronchiolar epithelia. The expression of cathepsin L was lost in some tumors (16.0%, 32/200). In adenocarcinomas, expression levels were significantly lower in high‐grade tumors than in low‐grade tumors (one‐way ANOVA, P  < 0.0500). Copy number alterations were found in 18.0% (36 [32 gain + 4 loss] /200) of lung tumors. No relationship existed between cathepsin L protein expression levels and the copy number of its gene locus (Spearman's rank‐order correlation, P  = 0.3096). Collectively, these results suggest that the down‐regulated expression of cathepsin L, which is caused by an undefined mechanism other than copy number alterations, is involved in the progression of lung adenocarcinomas.